Caracterización molecular para el manejo de la colección colombiana de musaceas - Sánchez, Inés; Gaviria Arias, Duberney; Gallego Sánchez, Gerardo J.; Fajardo, Diego; Valencia Montoya, Jorge Alberto; Lobo Arias, Mario; Tohme, Joseph M.; Roca, W. (1998)
The Musa germplasm bank established in Colombia has accessions tolerant to Yellow Sigatoka and is located at over 1310 meters above sea level. This germplasm has been characterized using morphological descriptors. However it is has been difficult to identify some accessions due to mutations and environmentally induced changes of some accessions. To solve this, we have used a recent molecular technique named AFLP. Two combinations of primers generating high polymorphism (EcoRI-AAG/MseI-CAT and EcoRI-AAG/MseI-CTT) were selected. UPGMA analysis grouped accessions contained genomes AA and AAA. The highest similarity index was found within the Cavendish group. Accessions containing the ABB genome showed different degrees of similarity allowing us to discriminate between Colombian accessions and those recently obtained from West Africa. Results obtained using AFLPs markers were used in conjunction with morphological descriptors, isozymes, agronomic traits and RAPDs markers in order to characterize in detail this Musa bank.